Forms of Representation in the Aristotelian Tradition. Volume One: Sense Perception - Toivanen, Juhana (Brill, 2022)
The trilogy Forms of Representation in the Aristotelian Tradition investigates how Aristotle and his ancient and medieval successors understood the relation between the external world and the human mind. It gives an equal footing to the three most influential linguistic traditions - Greek, Latin, and Arabic - and offers insightful interpretations of historical theories of perception, dreaming, and thinking. This first volume focuses on sense perception and discusses philosophical questions concerning the external senses, their classification, and their functioning, from Aristotle to Brentano.